Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
ĐK: \(x\ge\frac{1}{4}\)
Ta có \(A^2=4x+2\sqrt{4x^2-\left(4x-1\right)}=4x+2\sqrt{\left(2x-1\right)^2}\)
Với \(x\ge\frac{1}{2},A=4x+2\left(2x-1\right)=8x-2\)
Do \(A\ge0\) nên \(A=\sqrt{8x-2}\)
Với \(\frac{1}{4}\le x< \frac{1}{2},A^2=4x+2\left(1-2x\right)=2\)
Do \(A\ge0\) nên \(A=\sqrt{2}\)
\(A=\dfrac{2}{x-1}\sqrt{\dfrac{\left(x-1\right)^2}{4x^2}}=\dfrac{2}{x-1}\left|\dfrac{x-1}{2x}\right|=\dfrac{\left|x-1\right|}{\left(x-1\right)\left|x\right|}\)
\(B=\left(x^2-4\right)\sqrt{\dfrac{9}{x^2-4x+4}}=\dfrac{3\left(x^2-4\right)}{\left|x-2\right|}\)
a) Ta có: \(A=\dfrac{2}{x-1}\cdot\sqrt{\dfrac{x^2-2x+1}{4x^2}}\)
\(=\dfrac{2}{x-1}\cdot\dfrac{x-1}{2x}\)
\(=\dfrac{1}{x}\)
b) Ta có: \(\left(x^2-4\right)\cdot\sqrt{\dfrac{9}{x^2-4x+4}}\)
\(=\dfrac{\left(x-2\right)\left(x+2\right)\cdot3}{\left(x-2\right)^2}\)
\(=\dfrac{3x+6}{x-2}\)
\(\frac{2x-x-1}{3x^2-3x-x+1}\)
\(=\frac{x-1}{\left(x-1\right)\left(3x-1\right)}\)
\(=\frac{1}{3x-1}\)
\(5-4x-\sqrt{x^2+2x+1}\)
\(=5-4x-\sqrt{\left(x+1\right)^2}\)
\(=5-4x-\left|x+1\right|\)(1)
+) Với x < -1
(1) = 5 - 4x - [ -( x + 1 ) ]
= 5 - 4x - ( -x - 1 )
= 5 - 4x + x + 1
= 6 - 3x
+) Với x ≥ -1
(1) = 5 - 4x - ( x + 1 )
= 5 - 4x - x - 1
= 4 - 5x
5 - 4x - \(\sqrt{x^2+2x+1}\)
= 5 - 4x - \(\sqrt{\left(x-1\right)^2}\)
= 5 - 4x - x - 1
= - 5x + 4
A=2x-|2x+1|
TH1: x>=-1/2
A=2x-2x-1=-1
TH2: x<-1/2
A=2x+2x+1=4x+1